Clinical assessment of balance using BBS and SARAbal in cerebellar ataxia: Synthesis of findings of a psychometric property analysis - Stanley John Winser; Catherine M Smith; Leigh A Hale; Leica S Claydon; Susan L Whitney (World Scientific Publishing, 2018)
Background: In the previous psychometric analysis paper in our series for identifying the core set of balance measures for the assessment of balance, we recommended the Berg Balance Scale (BBS) and balance sub-components of the Scale for the assessment and rating of ataxia (SARAbal) as psychometrically sound measures of balance for people with cerebellar ataxia (CA) secondary to multiple sclerosis. Objective: The present study further examined the suitability of BBS and SARAbal for the assessment of balance in CA with regard to psychometric property strength, appropriateness, interpretability, precision, acceptability and feasibility. Methods: Criteria to fulfill each factor was defined according to the framework of Fitzpatrick et al. (1998). Based on the findings of our previous psychometric analysis, each criterion was further analyzed. Results: The psychometric analysis reported good reliability and validity estimates for the BBS and SARAbal recommending them as psychometrically sound measures; they fulfilled both criteria for appropriateness and interpretability, the measures showed evidence for precision and acceptability, and they were found to be feasible in terms of the time and cost involved for the balance assessment. Conclusion: We have provided evidence for the use of the BBS and SARAbal for the assessment of balance among people with CA.